Stormwater source control with infiltration wells under a new conception - Ferreira, Thays Santos; Barbassa, Ademir Paceli; Moruzzi, Rodrigo Braga [UNESP] (Assoc Brasileira Engenharia Sanitaria Ambiental, 2018)
The objective of this study was to evaluate a new concept of infiltration well as in loco stormwater drainage source control. This infiltration well, namely P-GHidro, has holes in the wall of the concrete rings, layer of gravel external to the rings in order to improve the water distribution, a geotextile prefilter on the cover, and additional filters on the bottom and on the sides between the gravel and the soil. An infiltration well common in San Carlos (P-SC), Sao Paulo, Brazil, was used as reference, and its construction uses concrete rings juxtaposed to the soil without side holes or prefilter. Six tests of simulated rain were performed for each design infiltration well. The experimental data of infiltrated water flow were modeled by Puls method. The hydraulic conductivity, constant or variable, was used as a model adjustment parameter to the experimental data, and the adjustment was assessed using the coefficients of determination (R-2) and Nash-Sutcliffe (NS). P-GHidro had a better performance in the stormwater infiltration, with stored volume and emptying times smaller than the P-SC. The modeling showed good adjustments to the experimental data for constant hydraulic conductivity (average R-2 = 0.92 and NS = 0.56) and even better adjustments for variable hydraulic conductivity (average R-2 = 0.97 and NS = 0.97).
Keywords: compensatory techniques; infiltration well; Puls method